2020
DOI: 10.31742/ijgpb.80.2.9
|View full text |Cite
|
Sign up to set email alerts
|

Independent segregation of qualitative traits and estimation of genetic parameters and gene action for some quantitative traits in guar (Cyamopsis tetragonoloba L. Taub.)

Abstract: Current study was undertaken to elucidate the inheritance qualitative traits namely, flower colour and leaf hairiness in two F2 populations comprising of 194 and 99 individuals with reference to yield and agronomic traits along with genetic parameters. The violet colour of flowers and leaf hairiness were dominant over white flower and smooth leaves, respectively. The 2-test revealed independent single gene inheritance for both the traits with joint segregation ratio of 9:3:3:1 in F2. Except for no. of pods pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…However, mutation breeding was followed in moth bean germplasm selections without any systematic hybridization program for genetic improvement. Only limited inheritance studies are available in guar (Mahla et al 2020;Sharma 2 et al 2021a;Chaudhary and Lodhi 1981;Ray and Stafford 1985), while such studies are absolutely lacking in moth bean.…”
Section: Short Research Articlementioning
confidence: 99%
“…However, mutation breeding was followed in moth bean germplasm selections without any systematic hybridization program for genetic improvement. Only limited inheritance studies are available in guar (Mahla et al 2020;Sharma 2 et al 2021a;Chaudhary and Lodhi 1981;Ray and Stafford 1985), while such studies are absolutely lacking in moth bean.…”
Section: Short Research Articlementioning
confidence: 99%
“…This plant has a high drought tolerance and is a good crop for semi-arid regions (Grover et al, 2016) and it is called Cluster bean because the pods and flowers appear at the leaf-stem junction (Abidi et al, 2015). Mahla et al (2020) reported due to the high industrial value and the sharp jump in demand, the cultivation of guar has also attracted the attention of farmers in the countries of Australia, Bangladesh, Myanmar, the United States of America, South Africa, Brazil, Congo and Sri Lanka. This plant grows in sandy loam soils with good drainage as well as in saline and relatively alkaline soils with a pH of 7.5 to 8.0 (Ghulam Nabi, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, in this study, guar is used as a legume for phytoremediation (Amin et al, 2018). Guar or cluster bean (Cyamopsis tetragonoloba L.) is a drought-resistant annual leguminous crop that is predominantly grown in India and Pakistan (Mahla et al, 2020). Guar is one of the unique beans with a large spherical endosperm that contains a signi cant amount of galactomannans, which are used in a variety of food and industrial uses.…”
Section: Introductionmentioning
confidence: 99%